MEMBER CHECKING: EVALUASI KUALITAS INFOGRAFIK TIRTO.ID DI LAYANAN JEJARING SOSIAL INSTAGRAM - Ridlo, M. Harun Rosyid (BBPPMPV Seni dan Budaya Yogyakarta, 2023)
The use of infographics has been increasingly popular on social networking services (SNS),especially on Instagram. On the other hand, infographics posting on Instagram faces somemajor challenges since it deals with various types of posts and user’s motivation. Tirto.id isone of Indonesian’ news platform which specifically uses Instagram to publish infographics.The problem is that Tirto.id often appends chartjunks to its visualization; however, it remainspopular among audiences. Hence, this study aims to determine the quality of Tirto.idinfographics. Infographic quality is determined through evaluations involving Tirto.idinfographics and their readers’ experiences. First, 23 (twenty-three) Tirto.id infographicswere evaluated for their information visualization. Then, the evaluation results were validatedbased on the experiences of 15 (fifteen) audiences through member checking. The findingsdemonstrate that Tirto.id infographics consist of content composed of various visual elementsand having specific function. The information in Tirto.id infographics was obtained fromTirto.id web page divided into two categories of information visualization. The readersexperienced two stages of perception and faced problems in understanding the infographics.Based on these findings, the evaluation results demonstrate that Tirto.id infographics have alack of clarity, precision, and efficiency. Meanwhile, readers’ interest depends on topics,information, illustrations, and data visualization in infographics.